Route-specific ecotoxicogenomic responses of the honey bee Apis mellifera to imidacloprid revealed by co-expression analysis - de Castro Lippi, Isabella Cristina; Afonso, Juliana; da Luz Scheffer, Jaine [UNESP]; Lima, Yan Souza [UNESP]; Alvarez, Marcus Vinícius Niz [UNESP]; Fortes, Marina Rufino Salinas; de Oliveira Orsi, Ricardo (Elsevier, 2025)
This study applies an ecotoxicogenomic approach to investigate the molecular impacts of imidacloprid, a systemic insecticide, on Apis mellifera, using RNA-sequencing data to construct co-expression gene networks. We hypothesised that oral and contact exposure routes elicit distinct transcriptomic responses, reflected in the structure and composition of route-specific co-expression networks. Imidacloprid exposure triggers alterations in multiple interconnected pathways, reflecting its widespread impact on essential processes. Two distinct networks were derived from ingestion and contact exposure trials, comprising 263 and 249 genes, respectively. Distinct molecular responses and hub genes were observed between ingestion and contact exposure routes, revealing route-specific mechanisms of imidacloprid toxicity in honey bees. Analysis identified key hub genes, such as Ac3, AChE2, A4, and ACSF2 in the ingestion network, and Cryl1, Apid1, Blop, and LOC100577632 in the contact network, implicated in essential processes including cellular signalling, energy metabolism, immune regulation, and sensory function. Functional enrichment revealed disruptions in critical biological pathways such as G protein-coupled receptor signalling, oxidative phosphorylation, and lipid biosynthesis. These perturbations suggest that chronic exposure to imidacloprid may compromise foraging behaviour, cognitive function, immunity, and overall colony health. By integrating transcriptomic and network-based analyses, this study offers new insights into the potential sub-lethal molecular effects of neonicotinoids on pollinators, reinforcing the need for sustainable pest management strategies and tighter pesticide regulations. Future research should further elucidate the specific roles of hub genes across different exposure scenarios to better inform conservation strategies and regulatory policies.